Solitary Extramedullary Plasmacytoma of the Thyroid Gland - M. Ridal; N. Ouattassi; T. Harmouch; A. Amarti; M. N. Alami (Case Reports in Otolaryngology)
Solitary extramedullary plasmacytoma of the thyroid gland is an uncommon condition. Up to date, its clinical pathological features are not fully understood. We present a case of an extramedullary nonmucosal plasmacytoma of the thyroid gland which is the first case with regional metastatic lymph nodes. This condition requires a scrupulous survey to rule out a metastatic multiple myeloma. Although localized forms management is still controversial, authors require combined approach for regional metastatic forms. The prognosis is favorable compared to solitary bone plasmacytomas or multiple myeloma.